Peran Genarasi Muda dalam Menjaga Nilai Demokrasi Pancasila di Era Digital - Andre Triana; Frety Damayanti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
Pancasila democracy places the people as the main subjects in national and state life. The rapid development of the digital era has brought significant changes to democratic practices through easier access to information and increased public participation in digital spaces. In this context, young generations have a strategic role as the group most adaptive to information and communication technology. This study aims to analyze the role of young generations in maintaining and strengthening the values of Pancasila democracy in the digital era. The research method used is a qualitative descriptive approach with a literature study. Data were collected from various sources, including books, scientific journal articles, and research reports relevant to digital democracy and youth participation. The findings indicate that young generations can actively contribute by improving digital literacy, increasing political participation through digital media, and utilizing digital platforms as tools for education and advocacy. Furthermore, young generations play an important role in countering misinformation, strengthening the values of social justice, unity, and critical awareness in accordance with Pancasila principles. However, challenges such as the spread of disinformation, social polarization, and limited critical thinking skills in digital spaces remain significant obstacles. Therefore, continuous democratic education and digital literacy are essential to enable young generations to become responsible agents of change in sustaining Pancasila democracy in the digital era.